New soliton solutions of the 2D‐chiral nonlinear Schrodinger equation using two integration schemes. (28th December 2020) - Ur Rehman, Hamood; Asjad Imran, Muhammad; Bibi, Musarat; Riaz, Maham; Akgül, Ali
Abstract : In this paper, the new exact solutions for 2D‐chiral nonlinear Schrodinger equation (CNLSE) are acquired using two proficient integration tool, namely, the new extended direct algebraic method (EDAM) and extended hyperbolic function method (EHFM). We develop soliton and some other solutions by utilizing the particular values for the parameters involved in these methods. These methods are devoted to secure different kinds of new soliton solutions as well as trigonometric and hyperbolic function solutions. Furthermore, for the physical representation of the obtained solutions of the CNLSE, various 2D and 3D graphs are presented.